CYBERSECURITY OF AUTOMATED WORKING TIME ACCOUNTING SYSTEM USING BIOMETRICS OF FACE - Остапец, Денис; Дзюба, Владимир; Капшученко, Дарья; Годун, Елизавета (SWorldJournal, 2020)
The paper considers the principles of building a secure system of accounting of working time (for example, the system of accounting of attendance by university students) using identification by facial biometrics. The introduction of such systems helps to